Seasonal dynamics of macrophytes and phytoplankton in shallow lakes: a eutrophication-driven pathway from plants to plankton? - Sayer, CD; Davidson, TA; Jones, JI (WILEY-BLACKWELL PUBLISHING, INC, 2010)
P>1. Seasonal relationships between macrophyte and phytoplankton populations may alter considerably as lakes undergo eutrophication. Understanding of these changes may be key to the interpretation of ecological processes operating over longer (decadal-centennial) timescales.2. We explore the seasonal dynamics of macrophytes (measured twice in June and August) and phytoplankton (measured monthly May-September) populations in 39 shallow lakes (29 in the U.K. and 10 in Denmark) covering broad gradients for nutrients and plant abundance.3. Three site groups were identified based on macrophyte seasonality; 16 lakes where macrophyte abundance was perennially low and the water generally turbid ('turbid lakes'); 7 where macrophyte abundance was high in June but low in August ('crashing' lakes); and 12 where macrophyte abundance was high in both June and August ('stable' lakes). The seasonal behaviour of the crashing and turbid lakes was extremely similar with a consistent increase in nutrient concentrations and chlorophyll-a over May-September. By contrast in the stable lakes, seasonal changes were dampened with chlorophyll-a consistently low (< 10-15 mu g L-1) over the entire summer. The crashing lakes were dominated by one or a combination of Potamogeton pusillus, Potamogeton pectinatus and Zannichellia palustris, whereas Ceratophyllum demersum and Chara spp. were more abundant in the stable lakes.4. A long-term loss of macrophyte species diversity has occurred in many shallow lakes affected by eutrophication. One common pathway is from a species-rich plant community with charophytes to a species-poor community dominated by P. pusillus, P. pectinatus and Z. palustris. Such compositional changes may often be accompanied by a substantial reduction in the seasonal duration of plant dominance and a greater tendency for incursions by phytoplankton. We hypothesise a slow-enacting (10-100 s years) feedback loop in nutrient-enriched shallow lakes whereby increases in algal abundance are associated with losses of macrophyte species and hence different plant seasonal strategies. In turn such changes may favour increased phytoplankton production thus placing further pressure on remaining macrophytes. This study blurs the distinction between so-called turbid phytoplankton-dominated and clear plant-dominated shallow lakes and suggests that plant loss from them may be a gradual process.